2018
DOI: 10.13057/biodiv/d200135
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of floristic diversity along altitude in the northern slope of the central Alborz Mountains, Iran

Abstract: Moradi H, Attar F. 2019. Comparative study of floristic diversity along altitude in the northern slope of the central Alborz Mountains, Iran. Biodiversitas 20: 305-312. The Alborz is one of two main mountain chains in the north of Iran. The flora and vegetation of the sub-alpine and alpine zone of the central Alborz are less known comparing to the vegetation of lower altitudes with Hyrcanain forests. In this study, floristic composition and life-form spectra were investigated along an altitudinal transect rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The prevalence of hemicryptophytes and chamaephytes in our study system follows our predictions, and it is consistent with their dominant role commonly observed in high mountain ecosystems [6,33,38,40,42,77,107]. In general, it has been observed that the proportion of hemicryptophytes increases with elevation [33,36,40,41,108] in response to increasing precipitation and decreasing temperature [40,108], with this life form being the most dominant at high elevations [109,110]. In accordance with this general pattern, in our study area the hemicryptophytes increased monotonically with elevation (as expected), representing almost 80% of the species at the highest altitudes.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of hemicryptophytes and chamaephytes in our study system follows our predictions, and it is consistent with their dominant role commonly observed in high mountain ecosystems [6,33,38,40,42,77,107]. In general, it has been observed that the proportion of hemicryptophytes increases with elevation [33,36,40,41,108] in response to increasing precipitation and decreasing temperature [40,108], with this life form being the most dominant at high elevations [109,110]. In accordance with this general pattern, in our study area the hemicryptophytes increased monotonically with elevation (as expected), representing almost 80% of the species at the highest altitudes.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, the abundance of Festuca ovina, Colpodium parviflorum, Alopecurus vaginatus, Trifolium medium, and Poa pratensis resulted in a large number of hemicryptophytes at 2100-3300 masl elevation. Mota et al (2017) and Moradi and Attar (2019) found that hemicryptophytes are the most dominant life forms at high elevations. The lower disturbance at higher elevations favors hemicryptophytes.…”
Section: Discussion Interrelation Between Species Composition and Elementioning
confidence: 99%